Pengembangan Model Pembelajaran Science ter-Integrasi Mathematics berbasis PBL - Yullys Helsa; Yanti Fitria (Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
AbstractThe purpose of this study was to develop a problem-based model of science and mathematics integration for use by PGSD students that were valid and feasible to use in learning, to find out the effectiveness of problem-based science and mathematics integration models for basic education developed and help students to understand mathematical concepts and the concept of science and accelerate student graduation. In this study, it has reached the design and develop stage, the product has been validated, but it still needs testing steps to see the effectiveness of the product produced. From the results obtained it can be concluded that the development of the Science and Math Integration Model Development Model is valid in the view of the validators. Keywords:Integrated, Science, Mathematic, PBL